Integrasi Teknologi Sistem Informasi dalam Pengembangan Materi Ajar Bahasa Interaktif untuk Siswa Sekolah Dasar - Imam Mualim; Rudi Hartono; Khoirul Anam; Najla Asyila (Lembaga Pengembangan Kinerja Dosen, 2025)
Advances in communication and information technology have led to changes in the way elementary school students learn, making it more interactive through the use of digital media. The purpose of this research is to create an interactive e-Module for Indonesian language lessons, focusing on the ability of fourth-grade students to identify main ideas and supporting ideas. This research uses the Four-D (4D) model, which consists of the Define, Design, Develop, and Disseminate steps. Research participants included fourth-grade teachers, expert validators, and 25 students from SD Negeri 3 Tambah Dadi. Data was obtained through interviews, observations, and questionnaires for expert validation and practicality trials by students. The validation results show that the e-Module is highly feasible based on assessments from media experts (4.7), material experts (4.7), language experts (4.0), and practitioners (4.8). Small and large group trials yielded an average practicality score between 4.6 and 4.63, which is categorized as very practical. The research findings indicate that interactive e-Modules can increase students' interest in learning, facilitate understanding of material, and provide support for independent learning with a digital literacy approach. Therefore, the interactive e-Module that has been created is very suitable as an alternative teaching material for Indonesian language lessons at the elementary school level.